The name "Salicornietum perennis" ("sensu lato") and global nomenclatural issues - del Arco Aguilar, Marcelino José; Izco, Jesus; Rodríguez Delgado, Octavio (Lazaroa, 2017)
The name Zygophyllo fontanesii-Sarcocornietum perennis is rejected as it is invalid and the new name Halimiono portulacoidis-Salicornietum perennis is proposed with two subassociations: typicum and limonietosum canariensis. The name Salicornietum perennis for Cuban communities is corrected to Salicornietum ambiguae.